Mechanistic evaluation of the transfection barriers involved in lipid-mediated gene delivery: Interplay between nanostructure and composition - Pozzi, D. (2013)
Here we present a quantitative mechanism-based investigation aimed at comparing the cell uptake, intracellular trafficking, endosomal escape and final fate of lipoplexes and lipid–protamine/deoxyribonucleic acid (DNA) (LPD) nanoparticles (NPs) in living Chinese hamster ovary (CHO) cells. As a model, two lipid formulations were used for comparison. The first formulation is made of the cationic lipid 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP) and the zwitterionic lipid dioleoylphosphocholine (DOPC), while the second mixture is made of the cationic 3β-[N-(N,N-dimethylaminoethane)-carbamoyl] cholesterol (DC-Chol) and the zwitterionic helper lipid dioleoylphosphatidylethanolamine (DOPE). Our findings indicate that lipoplexes are efficiently taken up through fluid-phase macropinocytosis, while a less efficient uptake of LPD NPs occurs through a combination of both macropinocytosis and clathrin-dependent pathways. Inside the cell, both lipoplexes and LPD NPs are actively transported towards the cell nucleus, as quantitatively addressed by spatio-temporal image correlation spectroscopy (STICS). For each lipid formulation, LPD NPs escape from endosomes more efficiently than lipoplexes. When cells were treated with DOTAP–DOPC-containing systems the majority of the DNA was trapped in the lysosome compartment, suggesting that extensive lysosomal degradation was the rate-limiting factors in DOTAP–DOPC-mediated transfection. On the other side, escape from endosomes is large for DC-Chol–DOPE-containing systems most likely due to DOPE and cholesterol-like molecules, which are able to destabilize the endosomal membrane. The lipid-dependent and structure-dependent enhancement of transfection activity suggests that DNA is delivered to the nucleus synergistically: the process requires both the membrane-fusogenic activity of the nanocarrier envelope and the employment of lipid species with intrinsic endosomal rupture ability.